Sistema orgânico de produção de pescado de água doce - Boscolo, Wilson Rogério; Feiden, Aldi; Neu, Dacley Hertes; Dieterich, Fabiana [UNESP] (My University, 2012)
This study aimed to collect data about organic production of freshwater fish. Today the production of organic food of plant origin is predominant in the market, however, the animal rearing with organic certificate has great potential, and is an important tool for adding value to grains and organic products. Regarding the regulation of organic aquaculture, producers are based on international standards. In Brazil, the norms for breeding are very recent and their regulation was consolidated through Interministerial Instruction No28, published on June 8, 2001 by Ministério da Agricultura, Pecuária e Abastecimento (MAPA) together with Ministério da Pesca e Aquicultura (MPA). In the literature there are few studies with organic fish farm, but according to available data, the rearing of species such as tilapia (Oreochromis niloticus), pacu (Piaractus mesopotamicus) and jundia (Ramdhia sp) fed with organic diet, in different rearing systems, show results quite optimistic about the production system, which is the focus of this work.
Organic production system of freshwater fish
Keywords: Agro-ecology; Aquaculture; Livestock organic; Production system; Animalia; Oreochromis niloticus; Piaractus mesopotamicus; Tilapia